The Exposure to Divorce News on Social Media on the Decision to Postpone Marriage in Early Adulthood - Ruzan, Vidia Viddari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to determine the effect of exposure to divorce news on social media on the decision to postpone marriage in early adults in Banda Aceh City. The background of this study is the rapid development of information technology and social media that affects various aspects of life, including marriage. Based on data, there has been a significant increase in the divorce rate in Indonesia, including in Aceh, which is often reported on social media such as Instagram. This study uses a descriptive quantitative approach with a survey method using a questionnaire that assesses the frequency, duration, and attention of Instagram users to divorce news. The population of this study, namely early adults in Banda Aceh City, was 82,963 people with a sample taken of 100 people who were determined using the Slovin formula with a simple random sampling technique. The data analysis technique used is a simple linear regression test with the equation Y = 7,212 + 0.338X, the correlation coefficient value of 0.336, the coefficient of determination of 11.3% and hypothesis testing. The results showed that there was a significant effect of frequency, duration, and attention to the exposure of divorce news on Instagram on the decision to delay marriage in early adulthood in Banda Aceh City. This research is expected to contribute to the study of mass communication, especially related to the effects of social media on people's social behavior.